Perdebatan Etika Vs Hukum Sebagai Norma yang Memiliki Sanksi Mengikat Bagi Aparatur Sipil Negara (ASN) di Lingkungan Kementerian Keuangan - Putri, Bonita Cinintya (Jurnal Konstitusi & Demokrasi, 2021)
Ethics is an order of behavior based on a system of values in a particular society, which is more appropriate to be associated with science or philosophy. Therefore, ethics is more local or special. Ethical Philosophy not only pays attention to what is right or wrong, but also to good and bad judgments about things. The State Civil Apparatus has an important role in creating a law-abiding, modern, democratic, prosperous, fair and moral civil society in providing services fairly and equitably. Judicial institutions, in particular the District Courts, may not refuse to adjudicate a case submitted to them in accordance with the prevailing laws and regulations, on the grounds that there are no stipulating rules for adjudicating the case. Therefore, the purpose of this paper is to see the boundaries of a problem that binds civil servant employees brought into the realm of ethics and the realm of law (judicial). The existence of an article regarding unlawful acts causes many people to file a lawsuit to the District Court on the pretext of violating their rights but does not mention the elements of unlawful acts as stated in article 1365 of the Civil Code.